Destructive Journey of Phytophthora… Diversity in Phytophthora causing diseases in horticultural crops - Chowdappa, P; Janakiram, T (Indian Horticulture, 2019)
The Phytophthora species are major pathogens of many horticultural crops, causing incalculable losses. The genus Phytophthora is a destructive plant pathogen. Association of Phytophthora in destruction of citrus plants was recorded in 1836 in Azore island much before the potato famine in Ireland in 1845. However, scientific discipline of plant pathology born in early 1860s when Anton de Bary recognised the P. infestans as the pathogen causing potato late blight. Ever since, the genus was erected, several plant pathogenic species have been described. Only 59 Phytophthora species were recorded till 1996. Since then several new Phytophthora species have been described from different parts of the world. Now, 100 species have been recorded. The taxonomy of the genus has also undergone an evolution in the way it has been studied. Most of the species of the genus have wide host range, for example about 2,000 plant species are thought be to susceptible to infection by P. cinnamomi in Australia. There are also some species with narrow host range like P. sojae and P. infestans